Pemodelan Matematis Produk Domestik Regional Bruto Provinsi Sumatera Utara Berdasarkan Lapangan Usaha Dengan Regresi Linier Dan Nonlinier - Fahmi Kurniawan; Abil Mansyur (Jurnal Sains dan Teknologi, 2023)
Economic development is one of the important goals to be achieved by a country. Because basically economic development is an effort and policy with the aim of expanding employment opportunities, raising the standard of living of the people, and improving the regional regional economy. Gross Regional Domestic Product is an indicator that can be used to see economic growth in a region. North Sumatra's GRDP growth rate recorded in the Central Bureau of Statistics of North Sumatra has fluctuated. One way to find out if GRDP has increased or decreased is to use forecasting. In various fields, forecasting systems are needed that must be accurate to anticipate future events. One of the methods used is regression analysis, including polynomial and exponential regression, the data used is North Sumatra GRDP Growth Rate data from 2011 to 2021 where the X variable is the year and the Y variable is the GRDP growth rate each quarter, and the best method will be determined in this research. From the results obtained using the help of the Matlab application, the best forecasting model is by looking at the MSE which is close to zero where the MSE values are regression, namely: 1st Order Polynomial (MSE: 1.98e-05); Order 2 Polynomial (MSE: 0.0023); Order 3 Polynomial (MSE: 1.85e-04); Order 4 Polynomial (MSE: 12.65); Order 5 polynomial (MSE: 8.66); Exponential (MSE: 0.2447).